Development of Gel-in-Oil Emulsions for Khellin Topical Delivery - Joana Pereira; Rita Gonçalves; Margarida Barreto; Clarisse Dias; Fátima Carvalho; António J. Almeida; Helena Margarida Ribeiro; Joana Marto (MDPI AG, 2020)
Hypopigmentation is a progressive dermatological condition caused by a reduction in the skin pigment, melanin. Its treatment is considered a challenge due to the lack of a highly efficient single therapy. Currently, the main treatments include photochemotherapy, application of corticosteroids and immunosuppressants, and laser. Khellin-based gel-in-oil emulsions appear as a promising alternative since they ensure a concentration of the drug, a natural furanochromone, at the desired location, skin surface. Khellin promotes repigmentation as it forms a dark colored complex after solar irradiation. The aim of this study was the development and characterization (e.g., rheological behaviour, droplet size, tackiness, adhesion and spreadability) of three topical gel-in-oil emulsions prepared with different emollients, formulated through a cold emulsification process, and suitable for the incorporation of khellin. In vitro studies were performed to evaluate the drug release and permeation profiles across artificial membranes and excised human skin, respectively, using Franz-type vertical diffusion cells. The W/O emulsions developed showed macroscopic appearance, shear-thinning behavior with a mean droplet size from 3.28 to 4.28 μm, suitable for topical application. In vitro studies revealed permeation values of about 1% of khellin across the stratum corneum, making these gel-in-oil emulsions promising for preclinical and clinical studies. The cold process, being an easy and low energy production method, represents an innovative strategy to produce khellin-based gel-in-oil emulsions to treat patients with hypopigmentation.